Effects of increasing the degree of reasoning and the number of elements on L2 argumentative writing. (September 2019) - Rahimi, Muhammad
The impacts of task characteristics on second language (L2) writing require further exploration. This study examined the effects of increasing task complexity on L2 argumentative writing. Upper-intermediate L2 learners performed two writing tasks with varying degrees of complexity in relation to the number of elements and the degree of reasoning. The learners' writing was measured in terms of syntactic complexity, accuracy, lexical complexity, organization, content, and overall text quality. Increasing task complexity effected a significant desirable change in one dimension of syntactic complexity (notably the amount of subordination) and one dimension of lexical complexity (notably academic vocabulary use), had a significant adverse effect on accuracy, and led to the enhancement of content, organization, and writing quality. These findings lend support to the Trade-off Hypothesis, the Cognition Hypothesis, and the central tenet of Kellogg's writing model. Methodological and pedagogical implications of the study are also discussed.